Mothers’ Knowledge toward Maintaining Breast Milk Flow During Their High-Risk Neonates Hospitalization - Noor Thabit Abdalla; Zeki Sabah Musihb (Kufa Journal for Nursing Sciences)
Background: Breastfeeding is a part of the distinct bio psychosocial system of our species, which evolved over the course of mammalian evolution to enhance the health and survival of both infant and his mother. The act of breastfeeding involves much more than just passing breast milk from mother to children but vital aspect of a baby's upbringing from feeding the mother's breast.